2022
DOI: 10.1001/jamanetworkopen.2021.43955
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of Adverse Events in the Placebo Arms of COVID-19 Vaccine Trials

Abstract: IMPORTANCEAdverse events (AEs) after placebo treatment are common in randomized clinical drug trials. Systematic evidence regarding these nocebo responses in vaccine trials is important for COVID-19 vaccination worldwide especially because concern about AEs is reported to be a reason for vaccination hesitancy. OBJECTIVE To compare the frequencies of AEs reported in the placebo groups of COVID-19 vaccine trials with those reported in the vaccine groups. DATA SOURCES For this systematic review and meta-analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
103
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 54 publications
(118 reference statements)
5
103
0
7
Order By: Relevance
“…These results support the findings of our study that previous COVID-19 infection compensates for the decrease in antibody levels following vaccination, an effect that occurs primarily in the late phase beyond 90 days. In a recent systematic review and meta-analysis, significantly more ARs were reported in vaccine groups compared with placebo groups after COVID-19 vaccination trials, but the rates of reported ARs in the placebo arms were still substantial [ 32 ]. The result of this work is remarkable, however, the study did not examine the rate of seroconversion or subsequent antibody response in the placebo group and the vaccine group.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the findings of our study that previous COVID-19 infection compensates for the decrease in antibody levels following vaccination, an effect that occurs primarily in the late phase beyond 90 days. In a recent systematic review and meta-analysis, significantly more ARs were reported in vaccine groups compared with placebo groups after COVID-19 vaccination trials, but the rates of reported ARs in the placebo arms were still substantial [ 32 ]. The result of this work is remarkable, however, the study did not examine the rate of seroconversion or subsequent antibody response in the placebo group and the vaccine group.…”
Section: Discussionmentioning
confidence: 99%
“…One should note that this may not always be necessarily related to the vaccine constituents. Analysis of adverse events recorded in COVID-19 vaccine trials indicated that the rates of nocebo responses, i.e., unwanted effects seemingly elicited by placebo administration, are substantial [ 34 ]. This may be due to anxiety associated with intervention or misconceptions about potential side effects [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be that only more severe systemic side effects were proxy-reported in our study. However, the nocebo effect may also be relevant in explaining the discrepancy (i.e., that individuals warned of potential side-effects may report them even when receiving the placebo), with a recent meta-analysis reporting extremely common nocebo responses in trials of COVID-19 vaccines (76.0% of systemic effects after first dose and 51.8% after second dose) 28 .…”
Section: Discussionmentioning
confidence: 99%